Pengaruh Partisipasi Mahasiswa dalam Organisasi Ekstra Kampus terhadap Prestasi Belajar Mahasiswa STAI Kharisma Cicurug Sukabumi: The Influence of Student Participation in Off-Campus Organizations on Academic Achievement of STAI Kharisma Cicurug Sukabumi Students - Salwa, Siti; Rosadi, Adi; Aliyah, Adah; Yani, Ahmad; Sa'adiyah, Imas (Risalah Kharisma, 2025)
This research is motivated by the gap observed when students involved in extra-campus organizations are expected to enhance their academic achievement due to the numerous trainings and activities offered by these organizations. However, in reality, student participation in extra-campus organizations tends to hinder their academic performance. The purpose of this study is to determine whether student involvement in extra-campus organizations affects the academic achievement of students at Kharisma Islamic College, Cicurug, Sukabumi. The approach employed in this research is a quantitative approach, using descriptive quantitative methods. The sampling technique used is saturated sampling, with the population consisting of all students actively involved in extra-campus organizations, totaling 38 individuals. Data collection techniques in this research include questionnaires, observations, and interviews. Data were then analyzed using a simple linear regression technique. The results of the research indicate that there is no influence of student participation in extra-campus organizations on the academic achievement of students at Kharisma Islamic College, Cicurug, Sukabumi. This is based on a signification value of 0.050 ≤ 0.830 so that the result F is calculated ≤ F table, meaning that Ha is rejected and Ho is accepted.